Sámi concepts of pattern in the mathematics curriculum - Varjola, Carita Elisabeth Eira; Fyhn, Anne Birgitte; Siri, May-Torill (Svensk förening för matematikdidaktisk forskning (SMDF), 2022)
Norway’s new mathematics curriculum took effect in 2020. The word mønster (English: ”pattern”) appears 13 times in the curriculum text. This paper aims at providing insight into how the curriculum’s term ”pattern” can be translated into North Sámi in a way that supports a mathematics teaching rooted in local Sámi culture and language. Five Sámi words for patterns are analysed to highlight different meanings. The analysis reveals that minsttar is the word most frequently used in direct translations. A possible explanation for this is that the meaning of the word minsttar has evolved to cover more aspects of the meaning of ”pattern”. Context plays an important role in determining which Sámi word to choose; some words are for instance related to visual patterns and one is related to Sámi handicraft. The choices depend on what kind of pattern is examined. Because of language differences, it is important to translate ”pattern” with great care.